World Bank Equity Policy Lab Vulnerability Tool to Measure Poverty Risk - Gao, Jia; Vinha, Katja; Skoufias, Emmanuel (World Bank, Washington, DC, 2021)
Vulnerability to poverty refers to the likelihood that a household or an individual may fall below the poverty line in the event of a shock. Understanding vulnerability helps design policies to protect households and promote resilience. The World Bank's Equity Policy Lab (EPL) and the Global Solutions Group on the Welfare Implications of Climate Change, Fragility and Conflict Risks have developed a new tool to analyze the prevalence, causes, and sources of household vulnerability to poverty across different regions within a country. We use the example of Ethiopia to illustrate how countries can use the Vulnerability Tool to analyze vulnerability and adopt policies and programs to address it.